An iconographical interpretation of street art in Malaysia / Syafril Amir Muhammad...[et.al] - Muhammad, Syafril Amir; Mohd Din, Nurul Huda; Mahamood, Muliyadi; Mokhtar, Mumtaz (2016)
Street art in Malaysia began and active in the 1990s. It is an arena of public art activities such as façade of the buildings and ramparts. Style and method are similar like painting and normally it’s have meaning and definition afterward. This study will involve several towns in Peninsular Malaysia such as Kuala Lumpur, Shah Alam, Johor Bahru, Melaka, Ipoh and Penang. The aim of this study is to analyse the meanings and to recognize a contextual factor that influence the form and content of street art in Malaysia. Iconographical theory will be used to identify, classify and interpret the meaning and understand the phenomenon of street art in Malaysia. Comprehensive documentation will recognize and acquire a fresh perception of this trend.